Human Structural Variation: Mechanisms of Chromosome Rearrangements. Issue 10 (October 2015) - Weckselblatt, Brooke; Rudd, M. Katharine
Abstract : Chromosome structural variation (SV) is a normal part of variation in the human genome, but some classes of SV can cause neurodevelopmental disorders. Analysis of the DNA sequence at SV breakpoints can reveal mutational mechanisms and risk factors for chromosome rearrangement. Large-scale SV breakpoint studies have become possible recently owing to advances in next-generation sequencing (NGS) including whole-genome sequencing (WGS). These findings have shed light on complex forms of SV such as triplications, inverted duplications, insertional translocations, and chromothripsis. Sequence-level breakpoint data resolve SV structure and determine how genes are disrupted, fused, and/or misregulated by breakpoints. Recent improvements in breakpoint sequencing have also revealed non-allelic homologous recombination (NAHR) between paralogous long interspersed nuclear element (LINE) or human endogenous retrovirus (HERV) repeats as a cause of deletions, duplications, and translocations. This review covers the genomic organization of simple and complex constitutional SVs, as well as the molecular mechanisms of their formation. Trends: Breakpoint junction sequencing reveals the mutational mechanisms and complexity of structural variation (SV). Most human SV is generated via non-homologous end-joining and microhomology-mediated break-induced replication. Non-allelic homologous recombination between segmental duplications, LINEs, and HERVs drives recurrent SV. Chromothripsis is usually de novo, arises on paternal alleles, and in some cases is transmitted maternally.